Factors Affecting the Decision of Tourists Visiting the Tourism Object Laguna Beach, Kaur Regency - Chendy Afriza; Karona Cahya Susena; Andriyani Prawitasari (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The purpose of this study was to determine factors such as comfort, service quality and price influencing the decision of tourists to visit the Laguna Beach tourist attraction, Kaur Regency. The sample from this study was taken 50 people on Saturday and Sunday, so the number of samples in this study were 100 tourists who visited the Laguna Beach Tourism Object, Kaur Regency. Data collection using a questionnaire. In proving and analyzing the data used validity, reliability, multiple linear regression test and f test and t test. The regression results show that there is a positive influence between comfort, service quality and price on the decision to visit the Laguna Beach tourist attraction, Kaur Regency because the regression direction has a positive direction, namely Y = 16,288 + 0,252X1 + 0,317X2 + 0,244X3 + e. Comfort has a significant effect on the decision to visit the Laguna Beach tourist attraction, Kaur Regency, because the significant value of 0.000 is smaller than 0.05. This means that the better the comfort at the Laguna Beach tourist attraction, Kaur Regency, the decision to visit tourists will also increase. Service quality has a significant effect on customer satisfaction at the Laguna Beach tourist attraction, Kaur Regency, because the significant value of 0.005 is smaller than 0.05. This means that the better the quality of service at the Laguna Beach tourist attraction, Kaur Regency, the better the decision to visit tourists. Price has a significant influence on the decision to visit the Laguna Beach tourist attraction, Kaur Regency because the significant value of 0.000 is smaller than 0.05. This illustrates that as the price increases, the decision to visit tourists will increase. Convenience, service quality and price jointly have a significant effect on the decision to visit the Laguna Beach tourist attraction, Kaur Regency, thus the initial hypothesis proposed is proven (Ha accepted). The coefficient of determination of R square is 0.374. This means that comfort, service quality and price affect the decision to visit by 37.4% while the rest (100-37.4% = 62.6%) is influenced by other causal factors not examined in this study.